Clinical Effects of Krachaidum (Kaempferia parviflora): A Systematic Review. (July 2017) - Saokaew, Surasak; Wilairat, Preyanate; Raktanyakan, Paranya; Dilokthornsakul, Piyameth; Dhippayom, Teerapon; Kongkaew, Chuenjid; Sruamsiri, Rosarin; Chuthaputti, Anchalee; Chaiyakunapruk, Nathorn
Kaempferia parviflora (Krachaidum) is a medicinal plant in the family Zingiberaceae. Its rhizome has been used as folk medicine for many centuries. A number of pharmacological studies of Krachaidum had claimed benefits for various ailments. Therefore, this study aimed to systematically search and summarize the clinical evidences of Krachaidum in all identified indications. Of 683 records identified, 7 studies were included. From current clinical trials, Krachaidum showed positive benefits but remained inconclusive since small studies were included. Even though results found that Krachaidum significantly increased hand grip strength and enhanced sexual erotic stimuli, these were based on only 2 studies and 1 study, respectively. With regard to harmful effects, we found no adverse events reported even when Krachaidum 1.35 g/day was used. Therefore, future studies of Krachaidum are needed with regards to both safety and efficacy outcomes.